2009
DOI: 10.1200/jco.2008.19.8002
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Ixabepilone, Mitoxantrone, and Prednisone in Patients With Metastatic Castration-Resistant Prostate Cancer Previously Treated With Docetaxel-Based Therapy: A Study of the Department of Defense Prostate Cancer Clinical Trials Consortium

Abstract: These results suggest that the combination of ixabepilone and mitoxantrone is feasible and active in CRPC and requires dosing with pegfilgrastim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…On the basis of results from a randomized phase 2 study suggesting that ixabepilone and mitoxantrone with prednisone have noncross-resistance and a phase 1 trial of the ixabepilone and mitoxantrone with prednisone combination demonstrating surprisingly high activity, the present phase 2 trial was undertaken. 5 The ixabepilone and mitoxantrone with prednisone regimen was found to have significant activity, with a PSA response proportion of 45%, and an equally promising objective response proportion of 22%. The overall survival in this group of patients was 12.5 months.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the basis of results from a randomized phase 2 study suggesting that ixabepilone and mitoxantrone with prednisone have noncross-resistance and a phase 1 trial of the ixabepilone and mitoxantrone with prednisone combination demonstrating surprisingly high activity, the present phase 2 trial was undertaken. 5 The ixabepilone and mitoxantrone with prednisone regimen was found to have significant activity, with a PSA response proportion of 45%, and an equally promising objective response proportion of 22%. The overall survival in this group of patients was 12.5 months.…”
Section: Discussionmentioning
confidence: 98%
“…2 Mitoxantrone with prednisone is often used as second-line therapy but is associated with a PSA response rate of only 20%. 5 Ixabepilone also has a disappointing PSA response rate of 17% after docetaxel. The objective response rates associated with ixabepilone monotherapy and mitoxantrone with prednisone after docetaxel are also low at 4% and 10%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Phase II trials of the epothilone B analogue ixabepilone in patients with chemotherapy-naïve HRPC have shown PSA responses both in single agent therapy (3348%) and in combination with estramustine (69%) [Rosenberg et al 2007;Bhandari and Hussain, 2005;Hussain et al 2005]. These agents were therefore combined in a phase I study [Rosenberg et al 2009] which demonstrated significant anticancer activity and manageable tolerability, confirmed in a recently reported phase II trial at ASCO 2009 [Small et al 2009a].…”
Section: New Chemotherapeutic Agentsmentioning
confidence: 99%
“…Because of the different mechanisms of action and the lack of crossresistance between these regimens, Harzstark and colleagues investigated the regimens' additive or synergistic activity when administered together in men with metastatic CRPC who had progressed after three or more cycles of docetaxel [56,57]. In a phase I trial, patients received escalating doses of i.v.…”
Section: Docetaxel-resistant Crpcmentioning
confidence: 99%
“…In a phase I trial, patients received escalating doses of i.v. ixabepilone (20 -35 mg/m 2 ) plus mitoxantrone (8 -12 mg/m 2 ) on day 1 of a 21-day cycle plus continuous prednisone (5 mg twice daily) to define a maximum-tolerated dose for the combination [57]. Of the six patients treated with ixabepilone at a dose of 30 mg/m 2 plus mitoxantrone at a dose of 12 mg/m 2 , two experienced DLTs (grade 3 diarrhea and grade 4 neutropenia), and of the five patients treated with ixabepilone at a dose of 35 mg/m 2 plus mitoxantrone at a dose of 12 mg/ m 2 , another two experienced DLTs (both grade 4 neutropenia).…”
Section: Docetaxel-resistant Crpcmentioning
confidence: 99%